KORELASI ANTARA HISAB DAN RUKYAT DALAM PERUMUSAN PENANGGALAN HIJRIYAH - Muhammad Fadhil; Fatmawati; Muh. Soleh Ridwan (HISABUNA: Jurnal Ilmu Falak, 2022)
Researchers examine the correlation between the correlation between reckoning and rukyat in the formulation of the hijriyah calendar. This research is motivated by the debate among Muslims who always decorate the seconds before the entry of the month of Ramadan, Eid al-Fitr, and Eid al-Adha. The difference between the reckoning group and the rukyat group often raises questions and debates among Muslims about which of the two methods is correct. This study aims to examine various theories in the method of reckoning and rukyat in the formulation of the hijriyah calendar using a historical approach and a syar'i approach which later is expected to be able to find out the correlation between reckoning and rukyat so that later there will be no more distance between the two methods in order to create unity and unity in worship. Hisab and rukyat basically have no conflict and can be said to be one unit and have the same value. Therefore, it is appropriate for the government, namely the Ministry of Religion of the Republic of Indonesia. as the authority holder to be able to immediately take a firm stance in order to create unity and integrity. And as citizens, every group or mass organization should unite perceptions and eliminate group egos in order to create unity and unity in worship.